A randomized comparative study of intraocular pressure and hemodynamic changes on insertion of proseal laryngeal mask airway and conventional tracheal intubation in pediatric patients - Garima Agrawal; Munisha Agarwal; Saurabh Taneja (Wolters Kluwer Medknow Publications, 2012)
Objective: To assess the influence of proseal laryngeal mask airway (PLMA) insertion on intraocular pressure (IOP). Aim: We compared the effects of PLMA insertion and laryngoscopic intubation on IOP and hemodynamic response in pediatric patients. Background: Previous studies have shown that there is no hemodynamic response to PLMA insertion similar to classic LMA insertion, but there is no published report about the influence of PLMA insertion on IOP. Conventional laryngoscopic tracheal intubation evokes a rise in IOP and cardiovascular response and has been traditionally used to secure the airway in pediatric patients undergoing ophthalmic surgery. Materials and Methods: 59 patients, less than 14 years of age, scheduled for elective ophthalmic surgery were randomly divided into two groups, group P, in which the patient's airway was secured with PLMA (using introducer tool technique), and group T, in which the airway was secured with laryngoscopy-guided endotracheal intubation. Heart rate, blood pressure, and IOP were measured just before insertion of the airway device and subsequently three times at intervals of 1 min after insertion of the airway device. Results: In group T, there was a significant rise in IOP as well as hemodynamic parameters recorded. In group P, there was no significant rise in hemodynamic parameters, but a significant rise in IOP was found though the rise was less than in group T. Conclusion: We conclude that the PLMA use is associated with lesser cardiovascular response and rise in IOP as compared to tracheal intubation.